Zero‐Order Catalysis in TAML‐Catalyzed Oxidation of Imidacloprid, a Neonicotinoid Pesticide. Issue 34 (26th May 2020) - Warner, Genoa R.; Somasundar, Yogesh; Weng, Cindy; Akin, Mete H.; Ryabov, Alexander D.; Collins, Terrence J.
Abstract: Bis‐sulfonamide bis‐amide TAML activator [Fe4‐NO2 C6 H3 ‐1, 2‐( N COCMe2 N SO2 )2 CHMe] − (2 ) catalyzes oxidative degradation of the oxidation‐resistant neonicotinoid insecticide, imidacloprid (IMI), by H2 O2 at pH 7 and 25 °C, whereas the tetrakis‐amide TAML [Fe4‐NO2 C6 H3 ‐1, 2‐( N COCMe2 N CO)2 CF2 ] − (1 ), previously regarded as the most catalytically active TAML, is inactive under the same conditions. At ultra‐low concentrations of both imidacloprid and 2, 62 % of the insecticide was oxidized in 2 h, at which time the catalyst is inactivated; oxidation resumes on addition of a succeeding aliquot of 2 . Acetate and oxamate were detected by ion chromatography, suggesting deep oxidation of imidacloprid. Explored at concentrations [2 ]≥[IMI], the reaction kinetics revealed unusually low kinetic order in 2 (0.164±0.006), which is observed alongside the first order in imidacloprid and an ascending hyperbolic dependence in [H2 O2 ]. Actual independence of the reaction rate on the catalyst concentration is accounted for in terms of a reversible noncovalent binding between a substrate and a catalyst, which usually results in substrate inhibition when [catalyst]≪[substrate] but explains the zero order in the catalyst when [2 ]>[IMI]. A plausible mechanism of the TAML‐catalyzed oxidations of imidacloprid is briefly discussed. Similar zero‐order catalysis is presented for the oxidation of 3‐methyl‐4‐nitrophenol by H2 O2, catalyzed by the TAML analogue of 1 without a NO2 ‐group in the aromatic ring. Abstract : All or nothing kinetics : This TAML activator of peroxides catalyzes hydrogen peroxide‐mediated oxidative degradation of imidacloprid, a nasty neonicotinoid pesticide, which is normally very resistant to oxidation. Remarkably, the reaction rate is virtually independent of the TAML concentration although imidacloprid does not degrade without the catalyst. A quantitative kinetic model is presented that accounts for this uncommon behavior.